The effects of the incentive systems and organizational culture on strategy surrogation / Kazeem Olalekan Akinyele. - Akinyele, Kazeem Olalekan (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2019)
The purpose of this study was to investigate the impact of an important aspect of an organizational context, specifically organizational culture, and different types of compensation schemes on strategy surrogation. Strategy surrogation occurs when managers focus on the measures in the strategic performance measurement systems (SPMS) on which they are compensated and completely or partially lose focus on the overall strategic objectives of the organization. This study utilized a 2x2 between-participants experimental design that manipulates organizational culture (control-dominant vs. flexibility-dominant) and the type of compensation scheme (fixed pay vs. pay-for-performance). The study was conducted online with 80 participants from the Amazon Mechanical Turk (MTurk) as proxies for managers. The results show that employees operating under a control-dominant culture do not surrogate more than employees operating under a flexibility-dominant culture. Additionally, the type of organizational culture does not moderate the relationship between incentive systems and strategy surrogation. However, employees operating under a pay-for-performance compensation scheme significantly surrogate more than employees operating under a fixed pay compensation scheme. The study contributes to the incentives and organizational culture literature as well as strategy surrogation research by examining institutional factors that may inhibit or exacerbate surrogation. Additionally, the study contributes to the judgment and decision-making literature by highlighting employees’ decision-making outcomes under different compensation schemes.